Corporate governance in the New Zealand public health sector: a 152.785 research report presented in partial fulfilment of the requirements of the degree of Master of Management (Management) at Massey University, Albany, New Zealand - Whitfield, Kyle (Massey University, 2010)
This research report considers corporate governance within the public health sector, an area which has undergone significant changes in terms of structures, focus, and demand for service and funding. As there has been little research conducted in this specific area, the report?s major findings are based on a critical examination of the literature on governance in private and public sectors along with an analysis of the changes that have occurred in the New Zealand Health sector over time. A review of the governance literature provides evidence that good corporate governance, if it is initiated and maintained properly, has benefits that can be organisation wide. The literature review provides evidence that effective governance can enhance the outcomes in the New Zealand health organisations that are part of a sector that has undergone four major restructures since 1989. It appears that these restructures have largely been driven by post-election political ideology and in most cases the changes have had little success in improving corporate governance within this sector. This research report concludes that some small, but significant, changes are necessary if the effectiveness of District Health Boards is to be improved. This report suggests three key changes. The first is to improve the structure by introducing new governance positions within District Health Boards. This position is based at the executive level and offers impartial advice to the board on all corporate governance issues. The second suggestion is that boards need to increase their diversity in order to improve performance, especially in geographical areas which have a large proportion of Pacific and Asian communities. The final recommendation is that board members are offered individual remuneration linked directly to their attendance and performance. These three changes, in turn, will help District Health Boards to become more effective in the way they operate.
Keywords: Corporate governance; Public health; New Zealand; District Health Board; Boards of directors; DHB; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management